Cervical Cancer Knowledge, Attitudes, and VIA Willingness among Married Women - Shabrina Nadilah Zahra; Erny Kusdiyah; Hanina; Wahyu Indah Dewi Aurora; Nyimas Natasha Ayu Shafira (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2024)
ABSTRACT Background: Indonesia has the highest rate of cervical cancer in Southeast Asia. However, early detection through Visual Inspection of Acetate Acid (VIA) among Women of Childbearing Age (WCA) in Indonesia, including Jambi City, remains low. This research aims to determine knowledge and attitudes toward cervical cancer prevention, and the willingness undergo VIA examination among married WCA at the Kenali Besar Public Health Center in Jambi City. Methods: An observational-analytical study with a cross-sectional design was conducted using questionnaires. 110 samples were chosen by accidental sampling technique and analyzed using descriptive statistics. Results: Most participants were in early adulthood (52.7%), had secondary education (50.9%), were unemployed (59.1%), had sufficient knowledge (40%) and attitudes (51.8%), but low willingness for VIA (47.3%). The main reason for not undergoing VIA was the absence of symptoms (22.7%). Most who had VIA had only been tested once (70%), with all results negative (100%). Conclusion: The willingness to undergo VIA screening is still low. Increasing the VIA screening coverage requires the improvement of knowledge about cervical cancer and attitudes toward cervical cancer prevention through effective health promotion. Keywords: cervical cancer; women of childbearing age; VIA test; knowledge; attitudes; willingness; behavior